Are prophylactic antibiotics necessary prior to transarterial chemoembolization for hepatocellular carcinoma in patients with native biliary anatomy?. Issue 6 (7th March 2018) - Watchmaker, Jennifer M.; Lipnik, Andrew J.; Fritsche, Micah R.; Baker, Jennifer C.; Mouli, Samdeep K.; Geevarghese, Sunil; Banovac, Filip; Omary, Reed A.; Brown, Daniel B.
Abstract : Background and Objectives: Prophylactic antibiotics are frequently administered for transarterial chemoembolization (TACE) of hepatocellular carcinoma (HCC). In patients without previous biliary instrumentation, infection risk from TACE is low. We hypothesized that there is a negligible rate of infection in these patients without prophylactic antibiotics. Methods: We reviewed consecutive patients undergoing TACE between 7/1/2013‐6/15/2016. All patients had an intact Sphincter of Oddi, received no peri‐procedural antibiotics, and had 30+ days follow‐up. Level of arterial selection was recorded. Baseline Child‐Pugh (CP) and Barcelona Clinic Liver Cancer (BCLC) scores were recorded. The primary outcome measure was the absence of clinical or imaging findings of hepatic abscess within 30 days. Results: A total of 171 patients underwent 235 TACE procedures. CP scores were A ( n = 109), B ( n = 47), and C ( n = 15). BCLC scores were 0 ( n = 1), A ( n = 108), B ( n = 47), and C ( n = 15). TACE was performed segmentally ( n = 208) or lobar ( n = 27). Three patients died of non‐infectious causes before 30 days. No hepatic abscesses developed in evaluable patients: 0/232 infusions. Conclusions: In patients with HCC and an intact Sphincter of Oddi, TACE was performed safely without prophylactic antibiotics. The majority of the patients were BCLC and CP A/B. Additional study of BCLC and CP C patients is warranted.